Understanding of «Suffering», «Pain» and «Human Existence» in Psychoanalysis and Philosophy - Haroyan, Nelli (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
This article analyzes a unique aspect of human existence that occupies a central place in philosophical anthropology with its multiple meanings, contradictions, complexities and the impossibility of fully understanding its essence. The problem of the perception of life and death, the biological and psychological characteristics of human inferiority, the constant state of deficiency caused by the presence of a boundary that must be overcome to maintain life, as well as the awareness of the inevitability of the end of human existence are considered. The article provides a brief overview of the key components of human existence, such as suffering - a phenomenon that indicates the desire for transformation, the transition from existence to non-existence, as an experience of one’s own completeness and finitude. The tragedy of human existence and suffering is examined from the point of view of the philosopher-theologian G. Narekatsi. This state is a necessary condition of human existence, studied by existential philosophers. The specificity of the experience of pain is analyzed, which indicates that sensitivity to pain may be associated with cultural and ethnic characteristics of the individual. Pain is considered as an important characteristic of the evolution of the living world and a basic sign of human existence, which has a significant impact on his existence. In addition, the question of the meaning of life is considered in the context of various points of view of existential philosophers and psychoanalysts Keywords: philosophy, psychology, suffering, pain, human phenomenon, existentialism, psychoanalysis, cognition, life, drives.